1994
DOI: 10.1007/bf01091231
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and vitamin C from fruits and vegetables: Impact of intake variations on nitrate and nitrite excretions of humans

Abstract: The objective of the study was to determine nitrate + nitrite excretions of human subjects fed variable amounts of nitrates and nitrites and vitamin C from fruits and vegetables. During four, randomly-arranged experimental periods of seven days each, the 12 apparently healthy, adult human subjects consumed laboratory controlled, constant, diets which were systematically varied in kinds of fruits and vegetable to provide the four following variations: 414 mg nitrate + nitrite and 23 mg vitamin C, 412 mg nitrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The application of 0.1% CaHPO 4 in canned apples did not change sensory evaluation, while in canned pears no changes in overall acceptance scores were detected in 0.05% of CaHPO 4 . Time of treatment is another important factor in terms of the efficiency of CaHPO 4 in order to reduce nitrate content.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The application of 0.1% CaHPO 4 in canned apples did not change sensory evaluation, while in canned pears no changes in overall acceptance scores were detected in 0.05% of CaHPO 4 . Time of treatment is another important factor in terms of the efficiency of CaHPO 4 in order to reduce nitrate content.…”
Section: Resultsmentioning
confidence: 71%
“…Sensory evaluation of canned pears revealed that the overall acceptance in samples contained less than 0.05% CaHPO 4, similar to that of the untreated product, while a significant decrease in overall acceptance score was observed for treatment by 0.1% CaHPO 4 (P<0.05). This may suggest that 0.05% CaHPO 4 did not affect sensory attributes and no offflavor was produced in both types of canned products. The percentage of panelists who Volume 11, No 5, September-October2017; http://www.ijt.ir selected the product for purchasing was also considered in the questionnaire; more than 60% of panelists selected the canned apples and pears for purchasing (Table 2).…”
Section: Sensory Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…Nitrate contained in food is absorbed in the human body by the intestines, and the nitrate absorbed is secreted in the oral cavity as a component of saliva and is exhausted to outside of the body as a component of urine [1,2]. The nitrate secreted in the oral cavity is reduced to nitrite by nitratereducing bacteria [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that leafy green or root vegetables and drinking water are sources of nitrate that humans are exposed to (Cassens 1997b). Nitrates and nitrites are part of the nitrogen cycle of plants and are by-products of green plant photosynthesis (Bednar and Kies 1994). Fertilizer used on vegetables with nitrogen compounds, the genetics of plants, the maturity and environmental conditions plants grow in (lack of water, soil fertility) also can play a role in the amount of nitrate found in these foods (Wolff and Wasserman 1972).…”
Section: Endogenous and Exogenous Sourcesmentioning
confidence: 99%